Identification of Neuronal Cells in Sciatic Nerves of Adult Rats - Liu, Yisheng; Zhou, Songlin; Zhao, Lili; Gu, Xiaosong (Frontiers in Cellular Neuroscience, 2022)
Prior research generally confirms that there are no neuronal cell bodies in the adult sciatic nerve. However, we occasionally find some neuronal cells in the adult rat sciatic nerves, either intact or crush injured. By whole-mount staining and optical imaging of the hyalinized sciatic nerves for Stmn2 (a specific marker for neuronal cells), we found those neuronal cells with irregular distribution in the sciatic nerves in both crushed model and normal rats. We investigated the identity of those cells and establish a cultured sciatic nerve model. Immunohistochemistry evidences both in vivo and in vitro illustrated that some of those cells are mature neurons in the sciatic nerves. With single-cell sequencing of neuronal cells in adeno-associated virus (AAV) infected sciatic nerves, we identified some of those cells are a kind of neuronal stem-like cells. Then we constructed a Nestin-creERT2 rat line and traced those cells with fluorescence labeling which induced by tamoxifen. Interesting, we proved the neuronal stem-like cells could proliferate by combination the EdU incorporation with staining in the sciatic nerves of transgenic rats. Together, the discovery of neuronal cells in the adult sciatic nerves will make us aware of the distribution of neurons in the peripheral nervous system. Especially our data suggest that the neuronal stem-like cells could proliferate in the sciatic nerves of adult rats.